2010
DOI: 10.1099/vir.0.022525-0
|View full text |Cite
|
Sign up to set email alerts
|

Full genome sequence analysis of parechoviruses from Brazil reveals geographical patterns in the evolution of non-structural genes and intratypic recombination in the capsid region

Abstract: Due to high genome plasticity, the evolutionary fate and geographical history of picornaviruses is hard to follow. Here, we determined the complete coding sequences of eight human parechoviruses (HPeV) of types 1, 5 and 6 directly from clinical samples from Brazil. The capsid genes of these strains were not remarkably different from European, North American and Japanese HPeV. Full genome analysis revealed frequent intertypic recombination in the nonstructural genome region. In addition, evidence of recombinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…This is of significance as later studies have indicated that recombinants of HPeV3 may only emerge every 20 years or so, whereas recombinant strains of HPeV1, 2, 4, 5 and 6 appear to emerge roughly every 4 years192425262728. Some of those studies also looked at sequence variation in the structural region of HPeV1 and HPeV3 and estimated a substitution rate around 0.72% per year for HPeV1 and only 0.28–0.37% per year for HPeV31924.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is of significance as later studies have indicated that recombinants of HPeV3 may only emerge every 20 years or so, whereas recombinant strains of HPeV1, 2, 4, 5 and 6 appear to emerge roughly every 4 years192425262728. Some of those studies also looked at sequence variation in the structural region of HPeV1 and HPeV3 and estimated a substitution rate around 0.72% per year for HPeV1 and only 0.28–0.37% per year for HPeV31924.…”
Section: Discussionmentioning
confidence: 99%
“…Like other picornaviruses, recombination of HPeV often involves breakpoints at the very end of VP1 and thus may remove or add the RGD motif, or alternatively occur downstream in the non-structural coding region81920212223. Studies have indicated that recombinants of HPeV3 with other types may emerge less frequently and suggested that this may be due to a different cell tropism of HPeV3 compared to HPeV1, 2, 4, 5 and 6819242526272829.…”
mentioning
confidence: 99%
“…Genome walking was performed for the three samples as described previously [47, 48]. To obtain the complete genome, partial region of the 5’-UTR, VP2, VP1 and 3D were amplified using previously published assays [35–37].…”
Section: Methodsmentioning
confidence: 99%
“…One potential recombination event was found which occurred between the lineage of HPeV5 represented by the strain Br/53/2006 (HQ696575) and the lineage of HPeV1 represented by the strain BNI-788st (EF051629). Br/53/2006 was identified in fecal samples from patients with acute diarrhea in Brazil (11), while BNI-788st was isolated from the stool sample of a German patient in Hamburg (12). Bootscan analysis showed one potential breakpoint located at the border between the P2 and P3 regions.…”
Section: Genome Announcementmentioning
confidence: 99%